DEEP BRAIN STIMULATION IMPLEMENTATIONS OUTSIDE OF PARKINSON DISEASE, LITERATURE OVERVIEW AND FUTURE PROSPECTS - Mikołaj Moskwa; Maja Elertowicz; Magdalena Zięba; Szymon Rudawski; Patrycja Herod; Magdalena Morytko; Aleksandra Wójciak; Kateryna Shtohryn (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Since the introduction of deep brain stimulation (DBS) around 200 thousands of patients have been treated, with many proposed mechanisms such as enforcing electrical patterns, changes in neurotransmitters status and reversible inhibition of certain neural tracts. Since its key role in late stages of Parkinson disease, its success is being on the scope of being reproduced for the new ways to implement DBS to better patients’ lives in various neurological disorders. With the high cost being its limitation and ability to correct or discontinue one of advantages, establishing new indications is going to improve quality of this procedure.Aim of the study: This review focused on establishing evidence based knowledge about DBS utility in treating conditions outside of Parkinson disease spectrum and potential fields where data is yet required to obtain.Methods and materials: Researchers searched MEDLINE and SCOPUS databases for articles from past 5 years. Phrases : “ deep brain stimulation” “DBS”  were used and work that focused purely on Parkinson disease was excluded. Proper studies were selected and presented in this review.Conclusion: The convincing evidence was found to support the use of Deep brain stimulation in essential tremor, chronic pain, epilepsy, dystonia and obsessive compulsive disorder. The evidence supporting efficacy in Depression is only based on open label studies, with insufficient effort to prove it in blinded RCTs. The addiction indication is promising, however higher quality studies need to be obtained. DBS as treatment of Alzheimer is forming based on animal research and weak evidence only envisioning structural changes and singular evidence of patients improving, but without finding, at its current shape, clinical efficacy in meta-analysis or RCTs.